A randomised controlled trial of email versus mailed invitation letter in a national longitudinal survey of physicians. - Benjamin Harrap; Tamara Taylor; Grant Russell; Anthony Scott (PLoS ONE, 2023)
Despite their low cost, the use of email invitations to distribute surveys to medical practitioners have been associated with lower response rates. This research compares the difference in response rates from using email approach plus online completion rather than a mailed invitation letter plus a choice of online or paper completion. A parallel randomised controlled trial was conducted during the 11th annual wave of the nationally representative Medicine in Australia: Balancing Employment and Life (MABEL) longitudinal survey of doctors. The control group was invited using a mailed paper letter (including a paper survey plus instructions to complete online) and three mailed paper reminders. The intervention group was approached in the same way apart from the second reminder when they were approached by email only. The primary outcome is the response rate and the statistical analysis was blinded. 18,247 doctors were randomly allocated to the control (9,125) or intervention group (9,127), with 9,108 and 9,107 included in the analysis. Using intention to treat analysis, the response rate in the intervention group was 35.92% compared to 37.59% in the control group, a difference of -1.66 percentage points (95% CI: -3.06 to -0.26). The difference was larger for General Practitioners (-2.76 percentage points, 95% CI: -4.65 to -0.87) compared to other specialists (-0.47 percentage points, 95% CI: -2.53 to 1.60). For those who supplied an email address, the average treatment effect on the treated was higher at -2.63 percentage points (95% CI: -4.50 to -0.75) for all physicians, -3.17 percentage points (95% CI: -5.83 to -0.53) for General Practitioners, and -2.1 percentage points (95% CI: -4.75 to 0.56) for other specialists. For qualified physicians, using email to invite participants to complete a survey leads to lower response rates compared to a mailed letter. Lower response rates need to be traded off with the lower costs of using email rather than mailed letters.